The essential listening skills in the English Curriculum for middle school students in Riyadh and the impact of using interactive E- book in their development - Al- Khozim, Khaled Mohammed; Al- Nashwan, Noha Abdulaziz (Journal of Educational and Psychological Sciences, 2019)
The study aimed to recognize the required listening skills in the English course for middle school students in Riyadh city and the impact of using interactive E- book in their development. To achieve the objectives of the study, the analytical descriptive approach, and the semi- empirical experimental approach were used. The two study tools used are; the checklist of essential listening skills required to be improved among the students of first middle grade, pre and post application of listening skills test applied to the study sample. The two tools were applied to a simple random sample through a draw. The experimental group consisted of (23) female students and the control group consisted of (22) female students in the first middle grade. The study findings revealed the following: The experimental group acquired a total mean of (22.52) against the control group (19.71) in the post- test application. Despite the obvious difference in favor of the experimental group, the value is not statistically significant in the development of listening skills in the English language curriculum at the level of significance (α ≤0.05). In light of the study finding, a number of recommendations and suggestions were presented to activate the use of interactive e- book in the development of listening skills in the English language curriculum.